Myosin heads have a broad orientational distribution during isometric muscle contraction: time-resolved EPR studies using caged ATP. - Fajer, P G (1990)
To study the orientation of spin-labeled myosin heads in the first few seconds after the production of saturating ATP, we have used a laser flash to photolyze caged ATP during EPR data acquisition. Rabbit psoas muscle fibers were labeled with maleimide spin label, modifying 60% of the myosin heads without impairing muscle fiber biochemical and physiological activity (ATPase and force). The muscle bundles were incubated for 30 min with 5 mM caged ATP prior to the UV flash. The flash, from an excimer laser, liberated 2-3 mM ATP, generating maximum force in the presence of Ca2+ and relaxing fully in the absence of Ca2+. Control experiments, using fibers decorated with labeled myosin subfragment, showed that the flash liberates sufficient ATP to saturate myosin active sites in all regions of the muscle bundles. To increase the time resolution, and to minimize the time of the contraction, we followed in time the intensity at a single spectral position (P2), which is associated with the high degree of orientational order in rigor. ATP liberation produced a rapid decrease of P2 with liberation of ATP, indicating a large decrease in orientational order in both relaxation and contraction. This transient was absent when caged AMP was used, ruling out nonspecific effects of the UV flash and subsequent photochemistry. The steady-state level of P2 during contraction was almost as low as that reached in relaxation, although the duration of the steady state was much more brief in contraction. Upon depletion of ATP in contraction, the P2 intensity reverted to the original rigor level, accompanied by development of rigor tension. The steady-state results obtained in the brief contractions induced by caged ATP are quantitatively consistent with those obtained in longer contractions by continuously perfusing fibers with ATP. In isometric contraction, most (88% +/- 4%) of the heads are in a population characterized by a high degree of axial disorder, comparable to that observed for all heads in relaxation. Since the stiffness of these fibers in contraction is 80% of the stiffness in rigor, it is likely that most of the heads in this highly disoriented population are attached to actin in contraction and that most actin-attached heads in contraction are in this disoriented population.